Hot off the press: News-implied sovereign default risk - Chukwuma Dim; Kevin Koerner; Marcin Wolski; Sanne Zwart (European Investment Bank (EIB), 2022)
We develop a sovereign default risk index using natural language processing techniques and 10 million news articles covering over 100 countries. The index is a highfrequency measure of countries' default risk, particularly for those lacking marketbased measures: it correlates with sovereign CDS spreads, predicts rating downgrades, and reflects default risk information not fully captured by CDS spreads. We assess the influence of sovereign default concerns on equity markets and find that spikes in the index are negatively associated with same-week market returns, which reverses over the next week, indicating that investors might overreact to default concerns. Equity markets' reaction to default concerns is more pronounced and persistent for countries with tight fiscal constraints. The response to global, compared to country-specific, default concerns is much stronger, underlining the relevance of global "push" factors for local asset prices.
Keywords: F30; G12; G15; 330; Sovereign default; Credit risk; Equity returns; Machine learning; Naturallanguage processing; Early warning indicators